The Importance of Investigating the Stool Antigen Helicobacter Pylori in Children with Growth Failure Between 2-12 years - شريتح أحمد; غالية مازن; حديفة رؤى (Latakia University Journal -Medical Sciences Series, 2020)
Introduction: Helicobacter Infection is one of the most common chronic around the world, 50% of the world’s population is affected, the highest prevalence rate in Africa (79%) and the lowest rate in Australia (24.4%). The infection is mainly acquired in childhood, with a low spontaneous recovery rate. Human-to-Human transmission via the fecal-oral or oral-oral, oral contagious route is the most likely method of transmission. Objective: The objective is to study the prevalence of Helicobacter Pylori infection in the population of children attending the endocrine clinic at Tishreen University Hospital with growth failure from 2-12 years from beginning of February 2019 and through one year. Methods: The study sample included 144 children from the endocrine clinic after excluding 13 cases. The age of the sample patients ranged from 2-12 years and the average age was 8 years. Type of the study: cross-sectional study. The study observational included the children with growth failure attending the endocrine clinic at Tishreen University Hospital, measurements (height, weight, BMI) were taken and analyzes (TSH, Anti-TTG) were performed, the stool antigen Helicobacter Pylori was investigated to diagnose the infection. Results: The number of patients in the study was 131 children (79 male, 52 female), ranged their ages are 2-12 years, and the median ages is 8 years. The percentage of children with stool antigen positive (38.2%) and distribution was 68% male and 32% female with P-Value =0.001. The infection was higher at older ages (8-10) and (10-12) years the largest percentage 54% of children with stool antigen positive. The underweight and short statures were more pronounced in the infected compared to others non-infected. Conclusion: The Helicobacter infection remains a public problem in our country. The study found an important relation between H.P infection and growth failure, where growth failure was more severe in children with positive antigen H.P.